Reranking and Pro-poor Growth: Decompositions for China and Vietnam - Wagstaff, Adam (2012)
Reranking in the move from one income distribution to another makes it impossible to infer from changes in Lorenz and generalised Lorenz curves how income growth among those toward the bottom of the initial income distribution compares to that among those toward the top, and whether there has been income growth among those who were initially poor. Decompositions allowing for reranking indicate that economic growth in China and Vietnam has been better for households who were initially poor than changes in the Lorenz and generalised Lorenz curve and poverty growth curve would suggest.